All you need to know about sarcopenia: a short guide for an internal medicine physician in questions and answers - G. R. Bikbavova; M. A. Livzan; D. V. Tikhonravova (Бюллетень сибирской медицины, 2023)
Sarcopenia is associated with social, economic, and individual burdens, including loss of independence, poor quality of life, and disability. In a short period of time, ideas about sarcopenia transformed from geriatric syndrome to disease. Initially, sarcopenia was considered in the context of gradual age-related deterioration in the functioning of all physiological systems. Over the years, it became clear that it can develop a second time, as a consequence of various diseases and pathological conditions.To date, there have been no generally accepted diagnostic criteria for sarcopenia. There are several tests and tools available for screening sarcopenia, the choice of which depends on physical capabilities of the patient, capabilities of the medical institution, and the purpose for which it is detected (research or clinical practice).From the point of view of human health, sarcopenia increases the risk of falls and fractures; impairs the ability to perform daily activities; is associated with the progression of major diseases and cognitive impairments; leads to movement disorders; contributes to a decrease in the quality of life, loss of independence or a need for long-term care. The presence of sarcopenia increases both the risk of hospitalization and hospitalization costs.The aim of the literature review is to provide an analysis of up-to-date information on the causes, pathogenesis, screening, diagnosis, treatment, and consequences of sarcopenia, myosteatosis, and sarcopenic obesity. The search for literature containing information on relevant studies was conducted in PubMed and Google Scholar by the following keywords: sarcopenia, dynapenia, myosteatosis, sarcopenic obesity, nutritional status, malnutrition.